2021
DOI: 10.1681/asn.2020030239
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping CKD Patients by Consensus Clustering: The Chronic Renal Insufficiency Cohort (CRIC) Study

Abstract: BackgroundCKD is a heterogeneous condition with multiple underlying causes, risk factors, and outcomes. Subtyping CKD with multidimensional patient data holds the key to precision medicine. Consensus clustering may reveal CKD subgroups with different risk profiles of adverse outcomes.MethodsWe used unsupervised consensus clustering on 72 baseline characteristics among 2696 participants in the prospective Chronic Renal Insufficiency Cohort (CRIC) study to identify novel CKD subgroups that best represent the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…This approach would promote an alignment of the molecular profile of the trial participants with the mechanism of action of the investigational agent. Molecular categorization could be combined with consensus clustering based on clinical and laboratory data, as outlined here for nephrotic syndrome and recently applied to the CRIC cohort 65 for precise delineation of patient prognosis and optimization of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This approach would promote an alignment of the molecular profile of the trial participants with the mechanism of action of the investigational agent. Molecular categorization could be combined with consensus clustering based on clinical and laboratory data, as outlined here for nephrotic syndrome and recently applied to the CRIC cohort 65 for precise delineation of patient prognosis and optimization of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It can search for similarities and heterogeneities among large categories of data variables and isolate them into clinically meaningful clusters [8,[15][16][17]. Recent studies have shown that disease subtypes determined by ML clustering methods can forecast different clinical outcomes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to assess similarities and differences in large datasets with many variables, and subsequently distinguish patients into novel clusters with distinct phenotypes [12,15,16]. Recent studies have demonstrated that ML consensus clustering can identify disease subtypes that carry different clinical outcomes [17,18].…”
Section: Introductionmentioning
confidence: 99%